2012
DOI: 10.1093/brain/awr361
|View full text |Cite
|
Sign up to set email alerts
|

Frontotemporal dementia with the C9ORF72 hexanucleotide repeat expansion: clinical, neuroanatomical and neuropathological features

Abstract: An expanded hexanucleotide repeat in the C9ORF72 gene has recently been identified as a major cause of familial frontotemporal lobar degeneration and motor neuron disease, including cases previously identified as linked to chromosome 9. Here we present a detailed retrospective clinical, neuroimaging and histopathological analysis of a C9ORF72 mutation case series in relation to other forms of genetically determined frontotemporal lobar degeneration ascertained at a specialist centre. Eighteen probands (19 case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

45
386
4
14

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 406 publications
(449 citation statements)
references
References 54 publications
(79 reference statements)
45
386
4
14
Order By: Relevance
“…These data reveal vulnerable neuroanatomical structures during the presymptomatic and symptomatic stages, which include ventral and dorsomedial prefrontal cortex, ventral and dorsal insula, anterior cingulate, caudate, and the medial thalamus. These regions are highly anatomically congruent with atrophy patterns found in C9orf72 ‐associated frontotemporal dementia 45, 47, 48, 49, 50. Notably, several studies confirmed that the medial thalamus is a region affected across C9orf72 expansion carriers,50 even during the presymptomatic phase 23, 36, 46.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…These data reveal vulnerable neuroanatomical structures during the presymptomatic and symptomatic stages, which include ventral and dorsomedial prefrontal cortex, ventral and dorsal insula, anterior cingulate, caudate, and the medial thalamus. These regions are highly anatomically congruent with atrophy patterns found in C9orf72 ‐associated frontotemporal dementia 45, 47, 48, 49, 50. Notably, several studies confirmed that the medial thalamus is a region affected across C9orf72 expansion carriers,50 even during the presymptomatic phase 23, 36, 46.…”
Section: Discussionsupporting
confidence: 65%
“…In parallel with the ROI analysis, the voxel‐wise analysis showed that certain sparse regions of lower grey matter volumes tended to associate with higher poly(GP), which included regions in the bilateral dorsolateral prefrontal, medial frontal, and lateral temporal cortices. Although higher poly(GP) levels showed a relatively weak association with lower grey matter volumes in our analyses, the regions identified include those atrophied in C9orf72‐ associated FTD patients,45, 47, 48, 49 and show reduced volume in presymptomatic C9orf72 expansion carriers 23, 36…”
Section: Discussionmentioning
confidence: 55%
“…Indeed, on the rare occasions this does occur it would appear that TDP‐43 is secondarily deposited upon pre‐existing DPR [14]. Second, despite there being reports of cerebellar atrophy in some cases with C9ORF72 expansions [25, 26], the presence of p62/DPR histological changes in this region appear clinically silent, at least when assessed using conventional measures of cerebellar function. This is despite present observations that DPR pathology appeared heavier within cerebellum than either cerebral cortex or hippocampus at early stages of the illness.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,5,6 Patients carrying the expansion can show heterogeneous clinical presentation, and the expansion has been identified in patients with other neurological diseases. 1,2,[7][8][9][10][11][12][13][14][15][16][17][18][19] Three potential pathomechanisms have been proposed to arise from the repeat expansion in C9orf72: RNAmediated toxicity through generation of RNA foci and sequestration of RNA-binding proteins from their normal targets; expression of dipeptide repeat proteins by repeatassociated non-ATG (RAN) translation; and haploinsufficiency. 1,2,[20][21][22][23] C9orf72 generates three transcripts through alternative splicing that encode 2 protein isoforms; a long isoform of approximately 54 kDa (termed C9-L), corresponding to variants 2 (V2) and 3 (V3), and a short isoform of approximately 24 kDa (termed C9-S) corresponding to variant 1 (V1).…”
mentioning
confidence: 99%